FANTASY YOGA EXERCISES THROUGH FABLE STORIES ON IMAGINATION OF EARLY CHILDHOOD - Veryawan, Veryawan; Pratiwi, Siti Habsari; Safira, Melda (UIN Fatmawati Sukarno Bengkulu, 2024)
Yoga is a holistic health system that is good for the soul, mind and body which is carried out with a smooth motion system that does not stomp with harmonious breathing guidance. The application of fantasy yoga exercises through fable stories is expected to increase children's imagination. The type of research used is qualitative research with the type of field research (field), the data collection technique that the author uses is observation, namely direct observation at the research location, with a total of 10 research subjects at Taman Indria Kindergarten. The results of the research obtained by children's imagination increased gradually by using fantasy yoga gymnastics through fable stories. This is based on the results of children's imagination through fantasy yoga exercises using fable stories at Taman Indria Kindergarten in general from the results of pre-cycle, cycle I and II on the indicator of knowing the instructions given by the teacher there was an increase of 55%, while on the right indicator of doing yoga gymnastics movements there was an increase of 35%, this also occurred in the indicator of children's skills in practicing the movement by 40% and the indicator of the ability to live the movement which increased by 42.5% and finally the child's ability to express the movement increased by 37.5%. This shows that children's imagination by using fantasy yoga gymnastics stories through fable stories at Taman Indria Kindergarten has increased.